Defining Power and Agency in Gender Relations in El Salvador: Consequences for Intimate Partner Violence and Women’s Mental Health - Navarro-Mantas, Laura; de Lemus, Soledad; García-Sánchez, Efraín; McGill, Lucy; Hansen, Nina; Megías, Jesús L. (Frontiers in Psychology, 2022)
Intimate partner violence (IPV) affects thousands of women around the world and is prevalent in the Global South. Unequal social structures perpetuate hierarchies and maintain women’s vulnerability to violence. Difficulties women face in accessing education, economic resources and employment diminish their power in intimate relationships, increasing the likelihood of intimate partner violence. These factors can also have a significant effect on women's mental health. However, some studies show that economic empowerment does not necessarily translate into greater agency for women if they cannot use the resources they earn to pursue whatever goals or values they regard as important in life. Agency is women’s ability to identify their life goals and act upon them through critical evaluation (intrinsic agency) and autonomous decision-making (instrumental agency). In this paper, we aim to analyze the relationship between women’s power (educational and economic) and agency and their influence on intimate partner violence, as well as on women’s mental health in the context of El Salvador. El Salvador currently has one of the highest percentages of femicide worldwide. We used data from the first national survey on violence against women in El Salvador to determine empowerment indicators and investigated their influence on intimate partner violence and women's mental health. Based on a representative sample of 1274 women between 15 and 64 years, using structural equation modeling, results revealed that education was a protective factor against IPV, but economic power appeared to put women at greater risk of IPV. Education was positively related to both intrinsic and instrumental agency, but only instrumental agency was negatively associated with the likelihood of being a victim of IPV. Finally, both intrinsic and instrumental agency were positively related to women's mental health. We discuss the importance of identifying specific factors related to women's power and agency to prevent IPV and mental health problems and to promote more gender equity in the Global South.